The effectiveness of the SQ3R and SQ4R methods on complementary therapy during pregnancy on student learning outcomes in Akademi Kebidanan Sentral Padang Sidempuan 2022 - Eliya Wardayani (Institute of Computer Science (IOCS), 2023)
Learning models that can be applied to improve students' ability to learn texts are the SQ3R (survey, question, read, recite, review) and SQ4R (survey, question, read, reflect, recite, review) learning models. These two methods are almost the same because SQ4R is a development of the SQ3R method. The purpose of this study was to determine the effectiveness of the SQ3R and SQ4R methods on complementary therapy material in pregnancy at the Padang Sidempuan Central Midwifery Academy in 2022. This study used a pre-experiment design with one group pretest-postest. The population was all midwifery study program students of the Sentral Padang Sidempuan Midwifery Academy. Sampling was carried out using purposive sampling technique on second semester students because second semester students were receiving Complementary Midwifery Care courses. Comparison of student learning outcomes using the SQ3R and SQ4R methods, SQ4R, SQ3R and without using the SQ3R and SQ4R methods shows that